Avaliação bioeconômica e de equações de predição de consumo de bovinos de corte em confinamento - Nichele, Evelyn Mangilli (2011)
Equations for predicting the consumption of dry matters of beef cattle finished in feedlot have been evaluated. Rate of 13.765 animals finished in a feedlot located in the North of Mato Grosso State in 2009 was collected. The rated data refer to crossbred male animals including the values of initial body weight, final live weight, average metabolic body weight and average daily gain, days of confinement and dry matter intake. The animals have been distributed in 123 groups, composed of 100 or 200 animals separated by categories based on body weight. The initial and final average body weights were 376,37 kg and 496,70 kg, respectively, with an average of 1,35kg of average daily gain and average permanence of 90 days. For prediction of DMI values six equations have been selected. They are based on average metabolic body weight, body weight and average daily gain. The evaluation of patterns has been carried out through the comparison between the predicted and observed DMI values. The prediction amplitude observed for the equations presented a variation between 7 to 11 kg/day of DM. Although equation DMI (kg/d) = -2,6098 + 0,08844MBW0,75 + 4,4672ADG – 1,3579ADG2 has presented lower dispersion (6.5 to 9.8 kg/d), the values of DMI predicted by the equation have not kept close to the ideal straight live. The equation of linear regression between the observed intake and the ones predicted by equation DMI (kg/d) = -2,6098 + 0,08844MBW0,75 + 4,4672ADG – 1,3579AADG2 indicates that the decline of the straight live obtained by the regression of the equation is the closest one to the ideal straight line (y=x), showing then that the equation has been appropriate to predict the DMI by the animals. Equations DMI (Kg/d) = -1,0094 + 0,01608MBW + 4,4363ADG -1,2548ADG2, DMI (Kg/d) = 3,73 + 0,0146BWi, DMI (kg/d) = 12,91 × [1 − e(−0,00295BWi)] e DMI (kg/d) = 1,8545 + 0,01937BWi have showed to be inappropriate to predict the dry matter intake of beef cattle fed with diets in tropical conditions in feedlot. Rate of 13.686 male bovines finished in confinement, during 2009, was used to analise the bio-economic efficiency. The efficiency of the animals has been evaluated through the following variations: daily gain, DMI, food conversion and nutritious efficiency. The sample was divided in two classes so called light class formed by oxen allotments weighing up to 350 kg of average live weight at slaughter and heavy class, composed allotments of animals over 350 kg of live weight. Thus four treatments have been arranged: dry season with the light weight class - DL; dry season with the heavy animals class - DH; rainy season with the light weight class - RL and rainy season with the heavy weight animals - RH. An analysis of varied multi variation has been carried out in order to discriminate the differences among the four treatments, considering all together: daily gain and total weight and total consumption of dry matter. Through the obtained results, we have observed that light animals present a higher bio-economic efficiency, better food conversion and better nutritious efficiency compared to the heavy animals what indicates that light animals in the beginning of the confinement still present corporal growth, reflecting on a better food conversion. As for the fattening season, the animals confined in the rainy season have not presented significant differences according to the rates of bio-economic efficiency, food conversion and nutritious efficiency, confirming that the finishing period in confinement does not influence upon the zootechnical and economical performance of fattening.